Community Choice Aggregation: Municipal Bulk Buying of Electricity in Massachusetts. - Laufer, Joshua.; McDonald, Betsy.; Pike, Brenda.; Zhou, Mengmeng. (Tufts University. Tisch Library., 2018)
2013 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Metropolitan Area Planning Council. This project is part of the Office of Sustainability Student Project Database, a place to share and view student projects related to sustainability and the environment.